Pengaruh Model Pembelajaran Berbasis Masalah terhadap Hasil Belajar IPAS Siswa Kelas V di SDN 7 Ampenan - Ghalby Khilafatulqudduus; Muhammad Sobri; Ilham Handika (Mataram University, 2026)
In elementary education, Science and Social Science (IPAS) learning is essential for developing students' critical thinking and integrated understanding of natural and social phenomena. However, conventional teacher centered instruction often leads to passive learning and suboptimal academic achievement among students. This study aims to examine the effect of the Problem-Based Learning (PBL) model on Science and Social Science (IPAS) learning outcomes of fifth grade students at SDN 7 Ampenan. A quantitative approach with quasi-experimental design (Nonequivalent Control Group Design) was applied. The sample consisted of 60 fifth-grade students divided into an experimental class (Class Va, n=30) receiving PBL instruction and a control class (Class Vb, n=30) receiving conventional teaching. Data analysis employed Kolmogorov-Smirnov normality test, Levene's homogeneity test, Normalized Gain (N-Gain) analysis, Independent Sample t-test, and Paired Sample t-test. Results revealed that the experimental group's mean posttest score (80.17) was significantly higher than the control group (68.30), reflecting an 11.87 point difference. N-Gain analysis yielded a mean of 0.438 (moderate category) for the experimental group and 0.158 (low category) for the control group. The Independent Sample t-test produced t = 6.711 with significance 0.000 (p < 0.05), leading to rejection of the null hypothesis. It is concluded that the PBL model significantly affects IPAS learning outcomes and is demonstrably more effective in enhancing students' cognitive abilities than conventional instructional methods.